Modified frontolateral partial laryngectomy operation: combined muscle-pedicle hyoid bone and thyrohyoid membrane flap in laryngeal reconstruction - Dian Ouyang (Cancer Biology & Medicine, 2013)
Objective:Laryngeal reconstruction is needed to preserve laryngeal function in patients who have undergone extensive vertical or frontal partial laryngectomy. However, the procedure remains a difficult challenge. Several reconstruction techniques have been described, but these techniques pose risks of complications such as laryngeal stenosis. This study aimed to evaluate the postoperative course and functional outcomes of a new technique that combined a muscle-pedicle hyoid bone and a thyrohyoid flap during laryngeal reconstruction after tumor resection. Methods:Four patients underwent extensive vertical partial or frontal partial laryngectomy for cancer. After tumor resection, laryngeal reconstruction was performed using the proposed technique. Postoperative recovery time, complications, and oncologic results were evaluated. Results:The four patients were successfully treated with the proposed technique. No dyspnea, dysphagia, or death occurred during the postoperative course. Decannulation was performed after a median of 3 days. The average postoperative hospital stay was 7 days. Short-term postoperative functional recovery was normal. No laryngeal stenosis or tumor recurrence was observed in any of the four patients after a follow-up period of more than 24 months. Conclusion:The combination of the muscle-pedicle hyoid bone and the thyrohyoid flap is a reliable procedure for laryngeal reconstruction after extensive vertical partial or frontal partial laryngectomy.